A history of Japanese cameras (Camerart Inc., 1976)
Contents:Part I and Part II, a History of Japanese Cameras, which CamerArt has been carrying for the past five years since the July 1976 issue, comes to an end. It has been compiled in the main by the Japan Camera and Optical Instruments Inspection and Testing Institute (JCII).